Trends in diet structural composition and quality among adults in Beijing, China (2010–2022) - Chen, Ningsu; Huang, Liyu; Zhao, Kai; Sha, Yimei; Zhao, Mengnan; Yao, Yihong; Qi, Yana; Zhang, Yan; Yu, Bo; He, Hairong; Yu, Jiajie; Duan, Jiali (Frontiers in Nutrition, 2025)
BackgroundUnbalanced dietary patterns are a major risk factor for chronic non-communicable diseases. Examining trends in population-level dietary structural composition and quality is essential for monitoring nutritional transitions, identifying key dietary risks, and developing targeted public health policies.MethodsThis study analyzed dietary trends among Beijing adults using three waves (2010–2022) of data from the China Nutrition and Health Surveillance (CNHS). Dietary intake was assessed through consecutive 3-day 24-h dietary recalls, supplemented by household weighing of cooking oils and condiments. Dietary structural composition was comprehensively analyzed, including the energy contribution of macronutrients and food sources of energy, protein, and fat intake. Population-level dietary quality was evaluated using the Chinese Diet Balance Index (DBI-22). Trend analyses were performed using the Jonckheere–Terpstra test, while group comparisons utilized chi-square and Mantel–Haenszel tests.ResultsA total of 4,520 participants were included. Between 2010 and 2022, carbohydrate contribution to energy intake decreased from 56.1 to 46.7%, whereas fat intake increased from 31.6 to 36.9%. A dietary shift from plant-based to animal-sourced foods was observed, with the latter demonstrating annual increases in their proportional contributions to total energy, protein, and fat intake (p for trend <0.001). DBI-22 assessments revealed persistent imbalances relative to dietary guidelines, with insufficient intake of vegetables, fruits, dairy, aquatic products, and soybeans (median scores: −1.5 to −6) and excessive intake of cereals, meat, eggs, oil, and salt (median scores: 1 to 4.7). Trend analyses indicated a worsening in excessive intake (p = 0.001) alongside a modest improvement in intake deficiency (p = 0.004) over the study period. However, the overall gap between the actual and recommended intake remains unchanged (p = 0.868). Subgroup analyses revealed stable dietary transition trajectories across population strata, with significant interaction effects between area and time observed for both dietary composition and diet quality (p for interaction <0.05), indicating divergent trends between urban and rural residents over time.ConclusionBetween 2010 and 2022, Beijing adults experienced substantial imbalances in dietary structure, characterized by decreasing energy intake from carbohydrates and increasing intake from fat, both diverging further from recommended levels. Dietary deficiencies and excesses coexist, contributing to suboptimal dietary quality compared with national dietary guidelines.